Emerging roles of hydrogel in promoting periodontal tissue regeneration and repairing bone defect - Guo, Wendi; Dong, Hongbin; Wang, Xing (Frontiers in Bioengineering and Biotechnology, 2024)
Periodontal disease is the most common type of oral disease. Periodontal bone defect is the clinical outcome of advanced periodontal disease, which seriously affects the quality of life of patients. Promoting periodontal tissue regeneration and repairing periodontal bone defects is the ultimate treatment goal for periodontal disease, but the means and methods are very limited. Hydrogels are a class of highly hydrophilic polymer networks, and their good biocompatibility has made them a popular research material in the field of oral medicine in recent years. This paper reviews the current mainstream types and characteristics of hydrogels, and summarizes the relevant basic research on hydrogels in promoting periodontal tissue regeneration and bone defect repair in recent years. The possible mechanisms of action and efficacy evaluation are discussed in depth, and the application prospects are also discussed.